ANALYSIS OF THE RELATION BETWEEN DECENTRALIZED STRUCTURE, BUDGETARY PARTICIPATION AND JOB RELEVANT INFORMATION, MANAGERS' VOI, AND ITS INFLUENCE TO JOB RELATED OUTCOME - JEFRY GASPERZ (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
This study analyses the relation of decentralised structure, budgetary participation to job relevant information, managers' VOI, and its influence to job related outcome (organisational commitment, job performance, job satisfaction). The respondents are middle-level managers and lower-level managers at State Owned Enterprises (BUMN). Data for the study was collected from 14 BUMN. The sampling method used is purposive sampling. In total 346 questionnaires were distributed, 135 an be used in analysis, with a response rate of 39,02 percent using strutural equation modelling of AMOS (Analysis of moment Structure) Program, the result of this study indicates that decentralised structure does not have significant influence to job relevant information, managers' VOI, and job performance. Budgetary participation has significant influence to job relevant information, managers' VOI, job satisfaction, and job performance. Job relevant information has significant influence on organisational commitment, job satisfaction, and job performance, while managers' VOI as significant influence on organisational commitment and job performance.